Convergent Synthesis of Two Fluorescent Ebselen-Coumarin Heterodimers - Jim Küppers; Anna Christina Schulz-Fincke; Jerzy Palus; Mirosław Giurg; Jacek Skarżewski; Michael Gütschow (Pharmaceuticals, 2016)
The organo-seleniumdrug ebselen exhibits a wide range of pharmacological effects that are predominantly due to its interference with redox systems catalyzed by seleno enzymes, e.g., glutathione peroxidase and thioredoxin reductase. Moreover, ebselen can covalently interact with thiol groups of several enzymes. According to its pleiotropic mode of action, ebselen has been investigated in clinical trials for the prevention and treatment of different ailments. Fluorescence-labeled probes containing ebselen are expected to be suitable for further biological and medicinal studies. We therefore designed and synthesized two coumarin-tagged activity-based probes bearing the ebselen warhead. The heterodimers differ by the nature of the spacer structure, for which—in the second compound—a PEG/two-amide spacer was introduced. The interaction of this probe and of ebselen with two cysteine proteases was investigated.